2016
DOI: 10.5539/gjhs.v8n12p266
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Written Prescriptions Received at Dental Laboratories in Tabriz, Iran

Abstract: <p><strong>AIM:</strong> This study was aimed at evaluating the quality of written prescriptions for fixed and removable prosthesis in Tabriz, northwest Iran.<strong></strong></p><p><strong>METHODS:</strong> To assess the quality of written prescriptions for fixed and removable partial dentures, a total of 600 questionnaires were distributed among 15 licensed dental laboratories receiving both fixed and removable prosthesis projects. The technicians were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…Overall, the results indicate poor quality of communicating design features for RPDs among dentists in Riyadh, Saudi Arabia. This is consistent with the findings of previous international studies ( 24 , 27 , 28 , 38 , 39 , 40 ). The quality scores of the provided instructions for RPD design were very low among the majority of the examined cases ( Table 4 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, the results indicate poor quality of communicating design features for RPDs among dentists in Riyadh, Saudi Arabia. This is consistent with the findings of previous international studies ( 24 , 27 , 28 , 38 , 39 , 40 ). The quality scores of the provided instructions for RPD design were very low among the majority of the examined cases ( Table 4 ).…”
Section: Discussionsupporting
confidence: 93%
“…Prescription of the type and position of the denture clasps was recorded in almost 20% of the cases (Table 3). This is compared to 47.7% in an Iranian survey (28).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this study 108 (43.9%) of the participants were capable of designing RPD frameworks independently. According to the result of the present study table 2 when the clinicians were asked about who is the responsible of surveying process 32 (13%) of the clinicians agreed that it's the job of the dentist, and 90 (36.6%) of the participants reported that the process of surveying is the respon- This survey outcomes are in contrary with the findings of earlier national [11] and international investigations [4,18,20,[22][23][24] who proved lack of responsibility toward design the RPDs and complete dependence on dental technician to design the RPDs. That resulted in poor RPD quality where Hummel et al in 2002 proved that two third of the worn RPDs are inadequate [25].…”
Section: Discussioncontrasting
confidence: 86%